An Energy-Efficient MAC Protocol Employing Dynamic Threshold for Wireless Sensor Networks. (17th October 2012) - Kim, Kyung Tae; Youn, Hee Yong
Abstract : Energy efficiency is a critical issue for sensor network since the network lifetime depends on efficient management of the energy resource of sensor nodes. Particularly, designing energy efficient MAC protocol has a significant influence on the performance of wireless sensor network with regards to the energy. The existing MAC protocols developed for sensor network try to avoid energy waste during idle listening time by controlling the duty cycle of the transmission period. Since the traffic conditions are diverse, they may not always display improvements in energy consumption. In this paper we propose a new energy efficient MAC protocol called dynamic threshold MAC (DT-MAC), which employs a dynamic threshold for the buffer of each sensor node to maximize the energy efficiency regardless of specific network traffic condition. Here the packets are stored in the buffer, and then transmitted when the number of packets in the buffer exceeds the threshold dynamically decided according to the number of hops of the node from the source in the path of packet forwarding. The simulation results using OMNnet++ show that DT-MAC enables significant improvement in energy consumption compared to the existing MAC protocols. The proposed DT-MAC protocol also reduces the number of transmissions of control packets.